Alexander the Great - Beddall, Fiona (Harlow : Pearson Education, 2008)
"Alexander the Great became king of Macedonia at the age of twenty. When he died, twelve years later, he ruled the biggest empire that the world had even known. Many people died as he and his army fought their way east. But he became a hero to many others, and his achievements were extraordinary."--P. [4] of cover
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Juvenile literature; Macedonia -- Kings and rulers -- Juvenile literature; Macedonia -- History -- To 168 B.C. -- Juvenile literature; Readers for new literates